2017
DOI: 10.1080/14786419.2017.1408103
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and pharmacological comparison of modern and traditional dosage forms of Joshanda

Abstract: Recently, a traditional remedy (Joshanda) has been replaced largely by modern ready-to-use dosage forms, which have not been compared to the original remedy. Therefore, the present study aimed to compare a number of modern dosage forms with traditional remedy. Seven brands, 3 batches each, were compared with a Lab-made formulation with reference to analytical (proximate analyses, spectroscopic and chromatographic metabolomes) and pharmacological profiles (anti-inflammatory and antibacterial activities). Chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Previous reports evaluated that the activity of the prepared extracts from the leaves and fruits depends on the active ingredients as well as the polarity of the ingredients [ 74 , 75 ]. In addition, several studies showed that the extracts of different polarity give potentially different pharmacological and toxicological activities [ 76 , 77 ]. Our results are in accordance to Al Mousa et al [ 78 ] who stated that the EA crude extract obtained from Alternaria tenuissima AUMC14342 gave the highest antimicrobial activity against P. aeruginosa , S. aureus , Fusarium solani , and Aspergillus niger at concentration 30 mg/mL using disc diffusion assay.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports evaluated that the activity of the prepared extracts from the leaves and fruits depends on the active ingredients as well as the polarity of the ingredients [ 74 , 75 ]. In addition, several studies showed that the extracts of different polarity give potentially different pharmacological and toxicological activities [ 76 , 77 ]. Our results are in accordance to Al Mousa et al [ 78 ] who stated that the EA crude extract obtained from Alternaria tenuissima AUMC14342 gave the highest antimicrobial activity against P. aeruginosa , S. aureus , Fusarium solani , and Aspergillus niger at concentration 30 mg/mL using disc diffusion assay.…”
Section: Resultsmentioning
confidence: 99%